PERAN TOKOH AGAMA DALAM MELESTARIKAN NILAI-NILAI TRADISI MAKAMAN DI DESA MEGU CILIK KABUPATEN CIREBON - nurhamzah, arief; Nasehudin, Nasehudin; Nurizzati, Yeti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
ABSTRACT Globalization has marginalized the Makaman Tradition, reducing its popularity and understanding of its values, which are now considered outdated and at risk of extinction. This study aims to identify the values within the Makaman Tradition in Megu Cilik Village, the role of religious leaders in preserving it, as well as the supporting and inhibiting factors. Religious leaders play a dual role as religious leaders and community development agents. A qualitative approach with ethnographic methods involved 3 religious leaders, 3 community members, neighborhood and community heads, and the village service chief. Data were collected through observation, document studies, and interviews. The study results reveal social values (mutual cooperation, charity, togetherness), cultural values (ancestor respect, religiosity, spirituality, etiquette norms), and religious values (obedience, faith, compassion). Religious leaders contribute through education, motivation, and exemplary behavior. Supporting factors include the active role of religious leaders and community enthusiasm, while inhibiting factors encompass the influence of changing times and ineffective distribution of blessings. Keywords: Role of Religious Leaders, Preserving, Makaman Tradition